ANALYSIS OF THE CURRENT STATE OF DEVELOPMENT OF SPEECH COMPETENCE BASED ON INTERDISCIPLINARITY IN MOTHER TONGUE CLASSES (Web of Humanities: Journal of Social Science and Humanitarian Research, 2023)
This article presents an analysis of the current state of development of speech competence in mother tongue classes based on the concept of interdisciplinarity. Speech competence refers to the ability to effectively communicate and express oneself orally in one's native language. Interdisciplinarity, on the other hand, involves integrating knowledge and methods from different disciplines to gain a deeper understanding of a particular subject.